Water cutting, stress hormones and salivary immunoglobulins in werstlers - Cieslak, T.; Muir, C.; Corbett, L.; Ludwa, I. A.; Klentrou, P. (International Journal of Fitness, 2011)
Intense training has been associated with increased stress and immune suppression in athletes. Testosterone (T) and cortisol (C) have been reported to suppress immunity while their ratio (T/C) has been used as an indicator of training induced stress. PURPOSE: The aim of this study was to determine if intense training coupled with dehydration methods implemented to lose weight prior to competition had an effect on the variability of stress hormones resulting in a suppression of salivary immunoglobulins in elite wrestlers. The hypothesis was that the variability (measured by %CV) of testosterone (T), cortisol (C) or T/C ratio might relate to salivary immunoglobulin counts. METHODS: Eleven elite wrestlers (21.3 ± 1.7 years of age) volunteered to participate in the study and were placed in either the experimental (WC; n=5) or the control (CO; n=6) group based on whether they were subjected to water cutting in preparation for an upcoming competition. Saliva samples were obtained at rest and 1-hr post-training over a two-week preparation cycle leading to competition. Resting samples were also obtained one day and two weeks following the competition. Saliva samples were assayed (ELISA) for T, C, and total antibody concentrations of both IgA and IgG classes. RESULTS: WC significantly decreased weight over the course of the study by 4.6 ± 1.4 kg. The 2-way repeated measures ANOVA revealed no significant day by group effects or interaction for resting antibody counts, T, C and T/C. Further pair-wise analysis showed significant post-training increases in IgA (2.2 ± 0.3 to 2.4 ± 0.3 ng/mL), IgG (1.2 ± 0.3 to 1.4 ± 0.4 ng/mL), T (283.8 ± 94.4 to 317.5 ± 92.4 pg/mL) and C (4.0 ± 1.6 to 4.8 ± 2.0 ng/mL) while a 9% decrease was found in post-training T/C. These post-training increases in T and C were higher in WC (19 and 28% for T and C, respectively) than CO (7 and 13% for T and C, respectively). The variability of post training T/C was related to both immunoglobulins at rest and after training indicating that higher the variability of T/C response, the lower the IgA and IgG. CONCLUSIONS: Rapid weight loss by prolonged dehydration seems to result in higher stress hormone variability in elite wrestlers. The continuous changing of the metabolic state of stress hormones might be a maladaptive response while a steady T/C ratio might enhance immunity in elite athletes.